The Types, The Function, and The Application of English Learning Media for Mute Students - Yohana Lolong Mena; I G A Lokita Purnamika Utami; Ni Luh Putu Era Adnyayanti (English Education Department STKIP Agama Hindu Singaraja, 2026)
This study aimed to analyze the types, functions, and implementation of English learning media for mute students at SLB Negeri 1 Buleleng. A qualitative case study design was employed to obtain an in-depth understanding of English teaching practices in a special education context. Data were collected through classroom observations, semi-structured interviews with the English teacher, and documentation of instructional materials. The data were analyzed using the interactive model of data reduction, data display, and conclusion drawing. The findings revealed that English instruction for mute students relied primarily on visual-based media, particularly written text, pictures, and diagrams. Written text functioned as the main medium for delivering English instruction, replacing spoken explanations, while pictures and diagrams were used to support comprehension of vocabulary and meaning. Visual learning media played a significant role in supporting students’ language acquisition by making learning content more concrete, meaningful, and easier to remember. Pictures helped students connect written English words with real objects, actions, or situations, thereby enhancing understanding and student engagement. Despite their effectiveness, several challenges were identified, including limited instructional facilities, students’ concentration difficulties during prolonged visual activities, and differences in students’ levels of visual comprehension. These challenges required teachers to adjust the teaching pace and provide repeated explanations using gestures or real objects. Overall, the study highlights the importance of visual-based instruction and appropriate learning media in supporting English learning for mute students in special school settings.